2017
DOI: 10.3390/ijms18030548
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Neurotrophins to Specific Populations of Neurons: NGF, BDNF, and NT-3 and Their Relevance for Treatment of Spinal Cord Injury

Abstract: Neurotrophins are a family of proteins that regulate neuronal survival, synaptic function, and neurotransmitter release, and elicit the plasticity and growth of axons within the adult central and peripheral nervous system. Since the 1950s, these factors have been extensively studied in traumatic injury models. Here we review several members of the classical family of neurotrophins, the receptors they bind to, and their contribution to axonal regeneration and sprouting of sensory and motor pathways after spinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
192
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(199 citation statements)
references
References 166 publications
(210 reference statements)
4
192
0
3
Order By: Relevance
“…This data is in line with previous observations that local NGF actions account for axon elongation 25 . Indeed, NGF-induced axonal sprouting in sensory neurons has been widely investigated, and NGF treatment probed in models of spinal cord injury 49 . Several aspects still need to be addressed, e.g.…”
Section: Resultsmentioning
confidence: 99%
“…This data is in line with previous observations that local NGF actions account for axon elongation 25 . Indeed, NGF-induced axonal sprouting in sensory neurons has been widely investigated, and NGF treatment probed in models of spinal cord injury 49 . Several aspects still need to be addressed, e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Our study indicated that AG1601 suppressed the proliferation of C6 glioma cells with dose and time dependence in vitro (Figure ). BDNF/TrkB/PI3k/Akt signal has great effects on the regulation of growth, development, and regeneration in neurons . Moreover, BDNF/TrkB/PI3K/Akt signal also could regulate the proliferation, apoptosis, invasion, and migration of many kinds of cancer cells, including breast cancer, multiple myeloma, and bladder tumor .…”
Section: Discussionmentioning
confidence: 99%
“…BDNF/TrkB/PI3k/Akt signal has great effects on the regulation of growth, development, and regeneration in neurons. 12,21 Moreover, BDNF/TrkB/PI3K/Akt signal also could regulate the proliferation, apoptosis, invasion, and migration of . BDNF, brain-derived neurotrophic factor; PI3K, phosphatidylinositol-3 kinases; TrkB, tropomyosin-related kinase B many kinds of cancer cells, including breast cancer, 23 multiple myeloma, 24 and bladder tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Controlled release of a biomolecule payload is of interest for inducing, enhancing, or selectively inhibiting cell growth along tissue scaffolds, and this is of particular interest in neuronal regeneration. [72] Protein-based therapeutics have posed one of the longstanding challenges in the area of drug eluting polymers, because the processing conditions used to prepare many bioresorbable polymer systems are incompatible with proteins, and the protein is often extensively denatured or hydrolyzed during formulation or during release. [7374] For these experiments we used lysozyme as a test protein because there is a standard and sensitive assay for lysozyme activity that allows convenient quantification of denaturation or other degradative processes that the protein might undergo.…”
mentioning
confidence: 99%